Surviving Cervical Cancer: Experiences of Women in the Accra Metropolis - Hobenu, K.A (University of Ghana, 2015)
Studies from other countries have provided evidence that women with cervical cancer encounter physical, psychological and social consequences. However, in Ghana, not much is known about the experiences of such women. Thus, the study explored the physical, psychological, social and spiritual well-being of women with cervical cancer in the Accra Metropolis, using the Quality of Life Model Applied to Cancer Survivors as an organising framework to understand their survival experiences. An exploratory descriptive qualitative approach with purposive sampling technique was used to elicit information from 15 survivors receiving treatment at the Korle-Bu Teaching Hospital. Interviews were conducted face-to-face and audio taped. Interviews lasted between 45 to 90 minutes. Data was transcribed verbatim and analysed using thematic content analysis. Five major themes were derived and described as follows: physical well-being of women with cervical cancer; psychological well-being of women with cervical cancer; social well-being of women with cervical cancer; spiritual well-being and coping strategies of women with cervical cancer; and health system factors. The study found that survivors of cervical cancer experienced both disease related symptoms and treatment consequences which resulted in poor physical well-being. Survivors experienced anxiety, depression, suicidal tendencies as well as impaired relationships, isolation and financial difficulties. Most survivors received support from spouses, family, workplace and health workers. Survivors prayed and had hope in God as a way of coping. Survivors lacked knowledge on the disease symptoms. Again, health workers did not provide information to survivors on the disease and side effects of treatment. There were also instances of misdiagnosis. It was recommended that a multi-disciplinary approach be used in managing cervical cancer survivors. There should be public awareness creation on the early signs and symptoms of cervical cancer.
Thesis (MPhil)- University of Ghana, 2015
Keywords: Cervical Cancer; Women Health; Non communicable Dieases; Misdiagnosis